Heart Failure Study: Profile of Heart Failure Admissions in Medical Intensive Care Unit - Regmi, Shyam Raj; Maskey, Arun; Dubey, Laxman (Nepalese Heart Journal, 2017)
Heart failure (HF) is a major cause of morbidity and mortality all over the world. In developed countries because of aging population and increased prevalence of coronary artery disease, heart failure has attained epidemic proportions, whereas, in developing countries like Nepal, rheumatic heart dissease is still the commonest cause of HF admission in medical intensive care unit (MICU). A retrospective study analysing registered data of HF admissions in MICU of Shahid Gangalal National Heart Centre (SGNHC) from August 2002 to OCtober 2008. Among these, 1771 patients were admitted for management of HF and were included in this study. Mean age was 45.07 Å} 35.09 (ranges from 11 years to 95 years). 836 (47%) were male and 935 (53%) were female. Rheumatic heart disease causing valvular cardiac lesion leading to HF was found in 791 (45%) patients. Dilated cardiomyopathy in 424 (24%), Ischemic heart disease in 378 (1%), hypertensive heart failure in 101 (6%) and HG due to congenital heart disease was found in 43 (2%) patients, Though, HF due to COPD / Cor-pulmonale is usually discouraged to be admitted in this heart centre, still 34(2%) patients were admitted for the management of HF due to COPD/cor-pulmonale. Rheumatic heart disease causing valvular cardiac lesion leading to HF admission was still the commonest cause of HF admission in MICU in our heart centre. Despite ACC/AHA guideline suggesting use of beta-blocking agent in patients with heart failure, only 22% of our patients received that agent. Thus, many patients were not being managed fully in accordance with international evidence based guidelines.